Deterring Rational Fanatics - Wilner, Alex S. (Book collections on Project MUSE., 2015)
Deterring Rational Fanatics provides a full-scale discussion of deterrence theory concepts and controversies, assessing the utility of relying on the logic of deterrence to counter contemporary terrorism. Alex S. Wilner's analysis shows that militant behavior can indeed be altered through the logic of deterrence.